Scl binds to primed enhancers in mesoderm to regulate hematopoietic and cardiac fate divergence. (7th January 2015) - Org, Tõnis; Duan, Dan; Ferrari, Roberto; Montel‐Hagen, Amelie; Van Handel, Ben; Kerényi, Marc A; Sasidharan, Rajkumar; Rubbi, Liudmilla; Fujiwara, Yuko; Pellegrini, Matteo; Orkin, Stuart H; Kurdistani, Siavash K; et al.
<x xml:space="preserve">Abstract</x> Previous work had revealed that Scl promotes hemogenic competence while repressing cardiac fate. Comprehensive genome‐scale data presented here establish Scl‐mediated 'enhancer decommissioning' as underlying molecular mechanism.